Notary’s Authority in Establishing Deeds for Minors and Their Rights as Shareholders of Limited Company - Desvia Winandra; Mohammad Fajri Mekka Putra (Faculty of Law, Universitas Pekalongan, 2023)
Notaries are empowered to demonstrate different types of business practices. One of the acts involves a shareholder taking legal action at the company. The laws and regulations in Indonesia do not regulate the age limit of shareholders. However, the result of the incompetent duty in this case is a child under the age of twenty- one and can apply for dismissal. This raises the issue of Notary’s authority to explain the claims of children who are unable to implement their rights as partners of a limited liability company. The normative legal method was used in this research. A child may be a legitimate shareholder, which is related to a person's legal conduct, that related to a person's legal actions and actions are seen from his skills and authority that was regulated in Indonesian Civil Code, the Law of Notary Position, and Indonesian Marriage Law. The attorney's authority over a minor child as a shareholder must be represented by his parents. Notary must focus on the skills and authority of the individual when exercising his position of drafting deeds or legal act on behalf of the company. Therefore, Notary must act diligently and thoroughly in drafting deeds and perform its position in accordance with the Law of Notary Position and the Notary Code of Ethics. Thus, Notary has the authority to establish deeds in a legal action for a twenty-one years old person as a company shareholder.